Experimental investigation of ignition delay and laminar burning velocity of HVO/RP-3 blends as a drop-in aviation fuel under extended operating conditions - Linlin Gu; Xunkai Hu; Chongyang Liu; Dongdong Qi; JingYu Ran; Zhongqing Yang (Fuel, 2027)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Structural stability-governed flavor binding: Unraveling flaxseed protein - aldehyde/pyrazine interactions by multispectral and molecular docking - Ran Zhao; Yini Yang; Yashu Chen; Lihua Huang; Yongjian Cai; Qi Zhou (Food Hydrocolloids, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Data-Driven Coastal Nutrients Estimation: Current Status, Research Gaps, and Future Developments - Sihan Ni; Jin Qi; Xiangbin Ran; Zhiqiang Liu; Sensen Wu; Minyu Wang; Keyi Yang; Chengfeng Le; Zhenhong Du (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Pressure-driven flavor formation in rapeseed oil: an integrated multi-omics approach - Yini Yang; Chang Zheng; Ran Zhao; Ya Xu; Lanhang Yao; Wenlin Li; Changsheng Liu; Chuyun Wan; Qi Zhou (Food Chemistry, 2026)

Metrnl in health and disease: tissue-specific actions and signaling networks - Ran Zhao; Yue Qi; Pan Li; Zhe Zhang; YiYang Chen; Xiaopeng Wu; Wei Wang; Xiaoqing Guo; Huadong Zhao; Yang Yang; Xiaowu Wang (Apoptosis, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

Dual-motor control of a flow-induced motion energy conversion system: Device development and experimental validation - Danjie Ran; Kainan Chen; Xiang Yan; Zuhao Zhang; Wene Wang; Yuanchun Qi; Xu Yang; Zhenyu Li (Ocean Engineering, 2026)

Pretreatment sequence of torrefaction and leaching for high–alkali biomass valorization: Focus on elemental migration, mineral evolution, carbon structure and torrefaction mechanism - Bowen Li; Junling Du; Rui Diao; Xu Hu; Cunzhang Yang; Ran Jiao; Fenglei Qi; Zhenting Zha; Xiaohao Liu; Peiyong Ma (Bioresource Technology, 2026)

Depleted uranium exposure induced ferroptosis in renal cells via the ETHE1/P38-MAPK pathway - Feng Huang; Wenrun Li; Juan Li; Yonghong Ran; Shiyan Fu; Li Shen; Qi Li; Xiaoyu Yang; Yazhen Zhao; Yuhui Hao (Archives of Toxicology, 2026)

Vessel Trajectory Anomaly Detection Based on Multi-scale Convolutional Autoencoder - Yuhao Qi; Jiaxuan Yang; Dongsheng Xu; Ran Shao; Yangyang Duan; Yangjie Wang (Ocean Engineering, 2026)

Responses of carbon monoxide photoproduction in surface seawater to environmental changes under simulated solar radiation - Xuan Ji; Ming-Liang Zhao; Yi-Ran Jia; Cai-Jie Zhang; Qi-Mei Du; Jing Zhang; Gui-Peng Yang (Marine Chemistry, 2026)

Sanguinarine inhibits bovine parainfluenza virus type 3 replication through CD97 suppression - Huasong Chang; Ran Kang; Rukun Yang; Wenjing Qi; Hongmei Wang; Hongbin He (Veterinary Microbiology, 2025)

PcUGT203E1 and PcUGT203B2 are involved in abamectin susceptibility in Panonychus citri - Yuchao Shen; Zehao Huang; Sichen Li; Wanfu Yao; Liu Liu; Shijun Fu; Shijiang Yu; Binbin Shao; Lili Ding; Qiqi Yang; Yang Li; Shaohui Zhang; et al. (Pesticide Biochemistry and Physiology, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

A gradient carbide-coated sialon nanowire for synergistic microwave absorption and toughening enhancement - Ran Wang; Jingwen Qi; Xueting Zhang; Yangkun Wang; Jiahao Qiu; Zihan Zhao; Yihan Chen; Pianpian Zhang; Xinyu Wang; Yanan Yang; Long Xia (Chemical Engineering Journal, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Multifunctional bending sensor based on PLA hierarchical porosity: smart wearable device with wide range response, self-powered capability and biodegradable - Jun Hou; Danqing Zhang; Qi Ran; Geran Yin; Manlin Wang; Wenhao Yang; Hua Wang; Yi Xiong; Xin Liu; Heng Pan; Liangjun Xia; Weilin Xu (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Vascular-tissue-specific expression of an endo-1,4-β-xylanase enhances forage efficacy of sweet sorghum silage - Fengyong Ge; Huimin Wei; Wenzhe Zhang; Cuo Mei; Yihong Gao; Hanlei Yang; Xuekai Wang; Jingwen Cao; Zhuolin Liu; Jiayang Shi; Ran Xia; Kangxu Zhao; et al. (Molecular Plant, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

CT2 is involved in yield-related traits and cell proliferation of maize - Yong Shi; Ran Xue; Qi Zheng; Zhanyong Guo; Chen Wang; Lanjie Zheng; Yankun Li; Jianping Yang; Weihuan Jin; Jihua Tang; Xu Zheng (Journal of Genetics, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Response of antibiotics and antibiotic resistance genes (ARGs) to a newly established stacked hybrid constructed wetlands with effluent recirculation operation - Jingmiao Fu; Yaqian Zhao; Jiafei Zhang; Yunv Dai; Qi Yao; Bin Ji; Yiping Tai; Ran Tao; Xiaomeng Zhang; Yang Yang (Journal of Water Process Engineering, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Tailoring hetero-precursor transformation for simultaneous surface-coating and subsurface-doping of Ni-rich layered oxide cathodes - Junfan Zhang; Ran Wang; Kunkun Guo; Mohan Yang; Zenan Zhao; Jing Wang; Qi Liu; Lai Chen; Ning Li; Yuefeng Su; Feng Wu; Guoqiang Tan (Chemical Engineering Journal, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Carboniferous, not Paleoproterozoic, eclogite-facies metamorphism in the northern North China Craton as revealed by in situ garnet Lu-Hf and U-Pb geochronology - Yao-Qi Yan; Hao Wang; Jin-Hui Yang; Shi-Tou Wu; Jing Ran; Bao-Quan Zhou; Ya-Dong Wu (Earth and Planetary Science Letters, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

Sustainable soil rehabilitation with multifunctional mandarin orange peel/tobermorite composite hydrogels: Water retention, immobilization of heavy metals, fertilizer release and bacterial community composition - Caiqing He; Xugang Wang; Haiyan Mou; Wenjing Hou; Qilu He; Yuchen Kang; Hao Kong; Ran Li; Wenqing Chen; Tianqi Ao; Shuanjun Li; Jian Yang; et al. (Chemical Engineering Journal, 2024)

Effects of plastic aging on biodegradation of polystyrene by Tenebrio molitor larvae: Insights into gut microbiome and bacterial metabolism - Meng-Qi Ding; Jie Ding; Shan-Shan Yang; Xin-Ran Ren; Shao-Nan Shi; Lu-Yan Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Science of The Total Environment, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Mechanism and ecological environmental risk assessment of peroxymonosulfate for the treatment of heavy metals in soil - Lai-Min Zhang; Lu-Lu Long; Qi-Ran Zhu; Chao Chen; Min Xu; Jun Wu; Gang Yang (Science of The Total Environment, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Influence of the community assemblage on sulfur distributions in the South China sea - Hao-Quan Zhang; Juan Yu; Jing-Guang Lai; Gui-Peng Yang; Long-Fei Liu; Yu Jiang; Xin-Ran Song; Yong-Qiao Chen; Hou-Jin Zhou; Qi Zhang (Marine Environmental Research, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

Optimizing Typha biochar with phosphoric acid modification and ferric chloride impregnation for hexavalent chromium remediation in water and soil - Yajun Cai; Jianwei Yang; Zhonglyu Ran; Fantong Bu; Xu Chen; Muhammad Shaaban; Qi-an Peng (Chemosphere, 2024)

Controls on apatite compositional variations in magmatic rocks: A case study of Mesozoic mafic–felsic intrusions from the eastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao (Journal of Asian Earth Sciences, 2024)

Soil Cd increased the leaf litter Cd remains of Solanum nigrum and Solanum lycopersicum - Qi Chen; Yuxuan Feng; Zunian Ran; Zeyan Zhou; Qianwei Li; Yunchao Luo; Sulin Cai; Siyuan Chen; Junbo Yang; Xingjun Tian (Environmental Pollution, 2024)

Biochar improved the solubility of triclocarban in aqueous environment: Insight into the role of biochar-derived dissolved organic carbon - Huiying Zhang; Weifeng Chen; Zhichong Qi; Wei Qian; Liumin Yang; Ran Wei; Jinzhi Ni (Chemosphere, 2024)

The effects of salinity stress on Crassostrea hongkongensis gill morphology, cell proliferation, and apoptosis - Chenyang Yue; Yiting Ran; Chuangye Yang; Salifu Ibrahim; Xinyu Song; Wengang Lü; Yuewen Deng; Qi Li (Aquaculture, 2024)

Recycled crustal components in the depleted mantle source: Evidence from Early Cretaceous mafic rocks in the southern margin of the North China Craton - An-Qi Wang; De-Bin Yang; Wen-Liang Xu; Hao-Tian Yang; Yi-Kang Quan; Xiang-Yu Yan; Le-Ran Hao; Feng Wang (Lithos, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

An artificial neural network-based machine learning approach to correct coarse-mesh-induced error in computational fluid dynamics modeling of cell culture bioreactor - Fernando José Cantarero-Rivera; Ran Yang; Haochen Li; Hairong Qi; Jiajia Chen (Food and Bioproducts Processing, 2024)

A glance of configuration-operational strategies and intensification of constructed wetland towards land-effective occupation - Jingmiao Fu; Yaqian Zhao; Yang Yang; Qi Yao; Bin Ji; Shanxu Chen; Yunv Dai; Ran Tao; Xiaomeng Zhang (Journal of Water Process Engineering, 2023)

Cutaneous Mucormycosis and Fusariosis in a Chinese Woman with CARD9 Deficiency - Lijun Zhou; Kaiwen Zhuang; Xinyu Qi; Ji Li; Dingbin Yang; Renheng Zhu; Guiying Guo; Jianjun Yang; Shuqiong Huang; Ran Yuping (Mycopathologia, 2023)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

Recent progress in γ-Fe2O3-based catalysts: An overview of the synthesis and applications in environmental remediation - Yuzhuo Zhou; Xin Yang; Chen Gong; Fei Zhu; Jian Wang; Yongfeng Qi; Kai Huang; Jiang Wu; Ran Chen; Yi Liu (Chemical Engineering Journal, 2023)

Identification of metasomatic components in lithospheric mantle under multiple tectonic regimes: Insights from Early Cretaceous mafic rocks in the northeastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Feng Wang (Lithos, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Environmental technical efficiency and its dynamic evolution in China's industry: A resource endowment perspective - Jun Yang; Ran Zou; Jixin Cheng; Zhifei Geng; Qi Li (Resources Policy, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

Molten NaCl assisted pyrolysis of ZIF-8/PAN electrospun fibers to synthesis 1D cross-linked mesoporous N-rich carbon as oxygen reduction electrocatalysts - Shuai Ran; Ji Qi; Xufeng Dong; Hao Huang; Min Qi; Wenjing Dong; Penghui Zhao; Zenghui Zhao; Jingyuan Yang (Chemical Engineering Journal, 2023)

Insights into the promotion of urine-diverting toilets based on the fertilizer efficiency of artificial phosphate ore recovered from source-separated urine - Yuan Liu; Qi Zhang; Lin-Feng He; Yang Ran; Ying-Ying Deng; Hong Liu (Resources, Conservation and Recycling, 2023)

Behaviour of double-corrugated steel plates under cyclic in-plane shear loading: An experimental study - Ran Deng; Jun-De Yang; Yuan Gao; Yu-Hang Wang; Qi-Qi Li (Engineering Structures, 2023)

Potential health and economic impacts of shifting manufacturing from China to Indonesia or India - Qi Ran; Shao-Yi Lee; Duofan Zheng; Han Chen; Shili Yang; John C. Moore; Wenjie Dong (Science of The Total Environment, 2023)

Apatite geochemistry from mafic rocks in the northeastern North China Craton: New insights into petrogenesis - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Hao-Tian Yang; Feng Wang (Lithos, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Isotopic and hydrochemical analyses reveal nitrogen source variation and enhanced nitrification in a managed peri-urban watershed - Fan Yang; Jianhua Guo; Ran Qi; Changzhou Yan (Environmental Pollution, 2023)

Establishment of regeneration system of Pyrus and the genetic stability analysis of regenerated population - Qi Liu; Yingjie Yang; Jianlong Liu; Jiankun Song; Dingli Li; Rencai Wang; Ran Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Elastic simulation method in an irregular polar coordinate system - Yu Yang; Qi Ran; Kang Chen; Cheng Lei; Yu-sheng Zhang; Song Han (Applied Geophysics, 2022)

Vegetation dynamics and its response to climate change during the past 2000 years in the Altai Mountains, northwestern China - Dongliang Zhang; Yunpeng Yang; Min Ran; Bo Lan; Hongyan Zhao; Qi Liu (Frontiers of Earth Science, 2022)

Overexpression of a putative 12-oxophytodienoate reductase gene, EpOPR1, enhances acetylshikonin production in Echium plantagineum - Jiangyan Fu; Ran Ren; Suo Jin; Rongjun Fang; Zhongling Wen; Minkai Yang; Xuan Wang; Bao Liu; Tongming Yin; Guihua Lu; Yonghua Yang; Jinliang Qi (In Vitro Cellular & Developmental Biology - Plant, 2022)

Regional seismic damage analysis considering soil–structure cluster interaction using lumped parameter models: a case study of Sichuan University Wangjiang Campus buildings - Bowen Zhang; Feng Xiong; Yang Lu; Qi Ge; Yang Liu; Zhu Mei; Mingming Ran (Bulletin of Earthquake Engineering, 2021)

Concatenated data and dense taxon sampling clarify phylogeny and ecological transitions within Hypotricha - Jiahui Xu; Mark Wilkinson; Miaoying Chen; Qi Zhang; Ran Yang; Zhenzhen Yi (Zoologica Scripta, 2021)
Ciliates are single‐cell eukaryotes playing important roles in various ecosystems. Phylogenetic relationships within Hypotricha, one of the most polymorphic and highly derived ciliate groups, remain uncertain. Previous studies suggested that low genetic divergence might be the reason for poorly supported SSU rDNA tree topologies, despite the high morphological diversity of this group. In this study, we substantially increase the number of available hypotrich LSU rDNA gene sequences by the addition of 857 environmental sequences, and we investigate whether a more divergent gene and dense taxon sampling could better resolve the phylogeny of Hypotricha and shed light on the patterns of ecological transitions in the evolutionary history of the group. Pairwise distances of LSU rDNA sequences are generally higher than those for SSU rDNA within each order of Hypotricha, and both concatenated rDNA and LSU rDNA trees provide more resolution for hypotrich phylogenetics. Three traditional (morphology based) hypotrich orders, Stichotrichida, Sporadotrichida and Urostylida, are polyphyletic, but a monophyletic core Urostylida are found in our trees. A brackish/marine environment is inferred as ancestral within Hypotricha, with subsequent ecological diversification into freshwater, soil environments before the origin of major clades and some transitions back to the marine. However, inferred ecological transitions in Hypotricha are influenced by genes, methods and taxa.

Suppression of coal dust by microbially induced carbonate precipitation usingStaphylococcus succinus - Wenjuan Song; Yuyi Yang; Ran Qi; Junpeng Li; Xiangliang Pan (Environmental Science and Pollution Research, 2019)

Antagonistic activity and protective effect of a Bacillus subtilis isolate against fish pathogen Edwardsiella piscicida - Xiaomeng Ren; Binbin Wu; Feng Zhao; Lingling Qi; Xianfeng Qiu; Ran Li; Sisi Yang; Fuguo Liu; Ganfeng Yi; Xuezhi Ding; Liqiu Xia; Yunjun Sun (Fisheries Science, 2019)

First identification of cucumber mosaic virus infecting six fruit crops in China - Cheng-Ming Yu; Guo-Wei Geng; Xin-Ran Cao; Chen Yang; Zhe Qi; Shan-Shan Liu; Chang-Xiang Zhu; Xue-Feng Yuan (Journal of Plant Pathology, 2019)

Mild Hypothermia Prevents NO-Induced Cytotoxicity in Human Neuroblastoma Cells Via Induction of COX-2 - Bing-Bing Lei; Fei Ju; Qi-Ran Fu; Xin Yuan; Wen-Xin Song; Guo-Qin Ji; Kai-Yu Lei; Lei Wang; Bin-Feng Cheng; Mian Wang; Hai-Jie Yang (Journal of Molecular Neuroscience, 2019)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

Ascomycotin A, a new citromycetin analogue produced by Ascomycota sp. Ind19F07 isolated from deep sea sediment - Yong-qi Tian; Xiu-ping Lin; Juan Liu; Kumaravel Kaliyaperumal; Wen Ai; Zhi-ran Ju; Bin Yang; Junfeng Wang; Xian-wen Yang; Yonghong Liu (Natural Product Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Spectroscopy and Molecular Docking Study on the Interaction Behavior Between Nobiletin and Pepsin - Hua-jin Zeng; Tingting Qi; Ran Yang; Jing You; Ling-bo Qu (Journal of Fluorescence, 2014)

Development of seventeen novel microsatellite markers of a wild and flowering bamboo Dendrocalamus membranaceus (Poaceae) and cross-amplification in Dendrocalamus genus - Yu-Ran Dong; Han-Qi Yang (Conservation Genetics Resources, 2014)

Biophysical studies on the interactions of jatrorrhizine with bovine serum albumin by spectroscopic and molecular modeling methods - Ran Mi; Pei-Qi Li; Yan-Jun Hu; Xiao-Yang Fan; Hai-Ying Li; Xue-Cheng Yu; Yu Ouyang (Molecular Biology Reports, 2013)